Optimal design for the flexural behaviour of glass and carbon fibre reinforced polymer hybrid composites - Dong, Chensong; Davies, Ian (Elsevier Ltd, 2012)
A study on the flexural behaviour of hybrid composites reinforced by S-2 glass and T700S carbon fibres in an intra-ply configuration is presented in this paper. The three point bend test in accordance with ASTM D790-07 at various span-to-depth ratios was simulated using finite element analysis (FEA). For the purpose of validation, specimens of selected stacking configurations were manufactured following the hand lay-up process and tested in a three point bend configuration. The validated FEA model was used to study the effects of fibre volume fractions, hybrid ratio and span-to-depth ratio. It is shown that flexural modulus increases when the span-to-depth ratio increases from 16 to 32 but is approximately constant as the span-to-depth ratio further increases. A simple mathematical formula was developed for calculating the flexural modulus of hybrid composites, given the moduli of full carbon and full glass composites, and the hybrid ratio. Flexural strength increases with span-to-depth ratio. Utilisation of hybridisation can improve the flexural strength. A general rule is in order to improve flexural strength, the fibre volume fraction of glass/epoxy plies needs to be higher than that of carbon/epoxy plies. The overall maximum hybrid effect is achieved when the hybrid ratio is 0.125 ([0G/07C]) when both Vfc and Vfg are 50%. The strength increases are 43.46% and 85.57% when compared with those of the full carbon and glass configurations respectively. The optimisation shows that the maximum hybrid effect is 56.1% when Vfc = 47.48% and Vfg = 63.29%.